2021
DOI: 10.1016/j.ctarc.2021.100339
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and cancer: A comparative case series

Abstract: Background Cancer patients, with an incidence of more than 18 million new cases per year, may constitute a significant portion of the COVID-19 infected population. In the pandemic situation, these patients are considered highly vulnerable to infectious complications due to their immunocompromised state. Material & Methods In this retrospective case series, the documents of solid cancer patients infected by SARS-CoV-2, hospitalized in Shariati hospital between 20 Februar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…15,17,23,29,33,39,43,50,51,56,61 Data from 30 studies revealed that gynecologic cancer had fewer Covid-19 death than lung cancer patients (OR 0.52, CI 0.44-.062, p <0.0001, I 2 0%) Figure 6A . 15,18-21,24-28,30,32,37,39,40-42,45,46,48-50,52-54,57,58 Data from 6 studies showed that gynecologic cancer was having less severity from Covid-19 than lung cancer (OR 0.36, CI 0.16-0.80, p 0.01, I 2 0%) Figure 6B . 24,25,32,53,54,60 Lastly, 2 studies reported fewer hospitalization associated with Covid-19 in gynecologic cancer than lung cancer (OR 0.54, CI 0.40-0.73, p <0.0001, I 2 0%) Figure 6C .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…15,17,23,29,33,39,43,50,51,56,61 Data from 30 studies revealed that gynecologic cancer had fewer Covid-19 death than lung cancer patients (OR 0.52, CI 0.44-.062, p <0.0001, I 2 0%) Figure 6A . 15,18-21,24-28,30,32,37,39,40-42,45,46,48-50,52-54,57,58 Data from 6 studies showed that gynecologic cancer was having less severity from Covid-19 than lung cancer (OR 0.36, CI 0.16-0.80, p 0.01, I 2 0%) Figure 6B . 24,25,32,53,54,60 Lastly, 2 studies reported fewer hospitalization associated with Covid-19 in gynecologic cancer than lung cancer (OR 0.54, CI 0.40-0.73, p <0.0001, I 2 0%) Figure 6C .…”
Section: Resultsmentioning
confidence: 99%
“…33,39,49,50,54,55 Gynecologic cancer had fewer Covid-19 associated death compared to other cancer according to 27 studies (OR 0.84, CI 0.72-0.97, p 0.02, I 2 4%) Figure 2. [18][19][20][24][25][26][27][28]30,32,37,[39][40][41][42]45,47,49,[51][52][53][54]56,57,59 Covid-19 associated severity was not statistically significant from 6 studies between gynecologic cancer and other cancer (OR 0.56, CI 0.30-1.03, p 0.06, I 2 0%) Fig. S8.…”
Section: Gynecologic Cancer Vs Other Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…2. [18][19][20][24][25][26][27][28]30,32,37,[39][40][41][42]45,47,49,[51][52][53][54]56,57,59 Covid-19 associated severity was not statistically signi cant from 6 studies between gynecologic cancer and other cancer (OR 0.56, CI 0.30-1.03, p 0.06, I 2 0%) Fig. S8.…”
Section: Gynecologic Cancer Vs Other Cancermentioning
confidence: 99%
“…6A. 15,[18][19][20][21][24][25][26][27][28]30,32,37,39,[40][41][42]45,[47][48][49][51][52][53]56,57 Data from 6 studies showed that gynecologic cancer was having less severity from Covid-19 than lung cancer (OR 0.36, CI 0.16-0.80, p 0.01, I 2 0%) Fig. 6B.…”
Section: Gynecologic Cancer Vs Lung Cancermentioning
confidence: 99%